Neoconservatism in Serbia - Vuletić, Vladimir (Sociološki pregled, 2020)
The text investigates the prevalence of neoconservatism among the population of Serbia, as an assumption enabling a political conservative turn. Having in mind that the evaluation of the prevalence of a phenomenon is a relational category, here the prevalence of neoconservatism has been measured, on one hand, in relation to the period of ten and/or fifteen years ago and, on the other hand, in relation to the current prevalence of other ideologies among the population of Serbia. The comparative framework has been constructed and measuring instruments have been adapted to secondary data collected within other studies.